Tool wear analysis of multi-layer diamond coated tools for cutting white marble. Issue 1 (March 2020) - Lu, F; Li, H X; Gabor, C; Wang, Y Y; Zhao, J B
Abstract: Study on the tool wear of cutting white marble by multi-layer diamond coated tool, and discussion of the wear characteristics and failure mechanism of the tool are presented in this paper. Multi-layer diamond coating was prepared by hot filament chemical vapor deposition (HFCVD). It was deposited on the surface of cemented carbide ball-end milling tool. The surface appearance of the tool was analyzed by an optical microscope. The grain state was analyzed by scanning electron microscopy. Comparing the surface morphology of the cutting for 1h, the area where the coating peeled off became larger when the cutting tool was cut for 2 hours, and the falling range was expanded along the cutting-edge direction while the flank surface was expanded, and the tool joint wear was severe. The composition of diamond grains was investigated by Raman spectroscopy. Comparing the surface morphology of the cutting for 1h, the area where the coating peeled off became larger when the cutting tool was cut for 2 hours, and the falling range was expanded along the cutting-edge direction while the flank surface was expanded, and the tool joint wear was severe.